Family-Friendly Support Programs and Work- Family Enrichment among Working Women: The Mediating Role of Organizational Perceptions - Hipiny, Noraini Binti Mohamad; Bandar, Nur Fatihah Abdullah; Daud, Awang Ideris Awang; Hassan, Zaiton; Eden, Dzulzalani; Jonathan , Victoria; Siong, Heng Chin (International Journal of Psychosocial Rehabilitation, 2025)
The study aims to examine the mediating role of family-supportive organizational perceptions (FSOP) between family-friendly support programs (FFP) (flexible work arrangements (FWA), specialized leave options, childcare facilities, financial supports, information and support and others) and work-to-family enrichment (WFE) (developmental-based, affective-based and capital-based) among working women. A quantitative methodology was adopted in this study in which data were gathered through survey questionnaires administered to 163 women employees working in two selected public institutions of higher learning in Sarawak, Malaysia. The hypotheses of the study were analysed using Pearson’s correlation analysis, multiple linear regression analysis and Sobel test. The results revealed that FSOP mediates the effect of the awareness on the availability of FWA and childcare facilities on WFE (affective based), which highlights the important role played by FSOP in determining the outcome of FFP. Hence, the adoption of work-life balance approach has to take into consideration the context in which it operates in as there is no ‘one size fits all’ approach that can meet the real needs of various cultures.